Acute MDMA and Nicotine Co-administration: Behavioral Effects and Oxidative Stress Processes in Mice - Budzynska, Barbara; Wnorowski, Artur; Kaszubska, Katarzyna; Biala, Grazyna; Kruk-Słomka, Marta; Kurzepa, Jacek; Boguszewska-Czubara, Anna (Frontiers in Behavioral Neuroscience, 2018)
Abstract 3,4-Methylenedioxy-methylamphetamine (MDMA), a synthetic substance commonly known as ecstasy, is a worldwide recreational drug of abuse. As MDMA and nicotine activate the same neuronal pathways, we examined the influence of co-administration of nicotine (0.05 mg/kg) and MDMA (1 mg/kg) on cognitive processes, nicotine-induced behavioral sensitization and on processes linked with oxidative stress and α7 nicotinic acetylcholine receptors (nAChRs) expression in the brain of male Swiss mice. For behavioral study the passive avoidance (PA) test and locomotor sensitization paradigm were used. Also, the oxidative stress parameters as well as expression levels of α7 nAChRs in prefrontal cortex and hippocampus of mice treated with MDMA alone or in combination with nicotine were assessed. The results revealed that MDMA injections as well as co-administrations of MDMA and nicotine improved memory consolidation in male Swiss mice tested in PA task. Furthermore, one of the main findings of the present study is that MDMA increased locomotor activity in nicotine-sensitized mice. Our study showed for the first time strong behavioral and biochemical interactions between nicotine and MDMA. Both drugs are very often used in combination, especially by young people, thus these results may help explaining why psychoactive substances are being co-abused and why this polydrug administration is still a social problem.